FANTASY GENRE: ARCHETYPES ALIVE IN MODERN DESIGN OBJECTS - Колосніченко , О. В.; Бризгунова , М. С.; Михайлюк , О. Ю.; Косточка , А. О. (Art and Design, 2023)
Purpose: to conduct an analysis of the main characteristic features of the fantasy style; to investigate its origins, development, manifestations and reflections in various artistic spheres; to reveal its role and reflection in modern design objects. Methodology. A comprehensive approach to the research of the development of the fantasy genre was used, which made it possible to single out its main categories, plot-thematic components and methods of classification. Historical and comparative methods made it possible to single out the main characteristics of the genre, the use of which gives stylistic unity to embodied fantasy images. Results. The peculiarities of the emergence and transformation of the fantasy genre as an independent component of artistic culture are considered. The specific features of the style and ways of their visual interpretation are defined. It is proved that the considered genre has gone through a long transformation path from imaginary literary images to stable archetypal associations. Scientific novelty of the study consists in a comprehensive approach to the study of the role of fantasy images synthesized from various artistic layers into integral modern archetypes that become an integral part of modern life. A semantic analysis of the means and stylistic trends of the fantasy genre was carried out. It is noted that the specificity of the genre, which consists in immersing the viewer in an unreal, imaginary, fictional world, contributes to its modern popularization and distribution. Practical significance of the study is due to the expansion of theoretical knowledge of the existence and development of the fantasy genre, its influence on consciousness and the formation of an alternative worldview by its supporters. The results obtained during the research made it possible to find out the origins and archetypes of the formed stable archetypes and can be applied in the development of modern design objects, in particular, clothing collections.